APPLICATION OF SKILL PLAY PUZZLES TO REDUCE ANXIETY IN PRESCHOOL CHILDREN AGED 3–6 YEARS OLD HOSPITALIZED IN THE WEST ASTER WARD OF DR. SARDJITO HOSPITAL, YOGYAKARTA - Arif Febrian; Sumarti Endah Purnamaningsih Maria Margaretha; Siti Wahyuni; Cindy Aulia Rachelli (Jurnal Kesehatan Karya Husada, 2025)
Background : Hospitalization is an unpleasant experience for children, often causing fear and anxiety. Anxiety in children must be addressed immediately as it can interfere with growth and development. Children need activities to help divert their fear and anxiety so they can manage these feelings effectively. Puzzle play is a beneficial form of play therapy for preschool-aged children. It is a simple associative game that involves assembling and disassembling puzzle pieces. When children engage in puzzle play, their focus shifts away from fear. Objective : To describe the application of puzzle skill play in reducing anxiety in hospitalized children aged 3–6 years in the Aster Barat Ward of Dr. Sardjito General Hospital Yogyakarta. Method : This study used a descriptive method to obtain a factual and accurate picture of the characteristics, facts, and relationships among the phenomena studied. Results : After four interventions over two consecutive days, each lasting 20 minutes, the anxiety scale decreased from an initial score of 41 (moderate) to a final score of 25 (mild). Conclusion : Puzzle skill play therapy is an effective non-pharmacological intervention to reduce anxiety in hospitalized children when applied four times over two consecutive days for 20 minutes per session.